2022
DOI: 10.1038/s41598-022-08945-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of plasma and fecal pharmacokinetics of danofloxacin and enrofloxacin in healthy and Mannheimia haemolytica infected calves

Abstract: Danofloxacin and enrofloxacin are fluoroquinolones (FQs) used to treat and control bovine respiratory disease (BRD) complex. While low toxicity, high bactericidal activity, and availability in single and multiple dosing regimens make them preferable, the increasing incidence of FQ-resistance in foodborne pathogens and effects on gut microbiota necessitate evaluating their pharmacokinetics (PKs). The objective of this study was to determine the exposure level of gut microbiota to subcutaneously administered FQs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…However, on DPI 19 (i.e., 72 h after the enrofloxacin injection), both the number of colonized calves and the magnitude of colonization (CFU/g feces) returned to the levels comparable to the pre-injection values and remained as such for the next 4 days until the end of the experiment. In line with these observations, fecal concentrations of enrofloxacin and its active metabolite ciprofloxacin were found to be at the peak levels (~20–40 µg/g) during the 12–24 h period after the antibiotic injection, and almost totally eliminated 48 h after the injection in all four treatment groups regardless of the dose administered or BRD status of the calves [ 43 ]. Interestingly and importantly, as shown by differential plating and MIC determination ( Figure 1 and Figure 2 ), the re-establishment of the colonization observed soon after the enrofloxacin injection (DPI 19 and beyond) in all of the calves in all four treatment groups was by FQ-susceptible C. jejuni .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…However, on DPI 19 (i.e., 72 h after the enrofloxacin injection), both the number of colonized calves and the magnitude of colonization (CFU/g feces) returned to the levels comparable to the pre-injection values and remained as such for the next 4 days until the end of the experiment. In line with these observations, fecal concentrations of enrofloxacin and its active metabolite ciprofloxacin were found to be at the peak levels (~20–40 µg/g) during the 12–24 h period after the antibiotic injection, and almost totally eliminated 48 h after the injection in all four treatment groups regardless of the dose administered or BRD status of the calves [ 43 ]. Interestingly and importantly, as shown by differential plating and MIC determination ( Figure 1 and Figure 2 ), the re-establishment of the colonization observed soon after the enrofloxacin injection (DPI 19 and beyond) in all of the calves in all four treatment groups was by FQ-susceptible C. jejuni .…”
Section: Discussionmentioning
confidence: 65%
“…The results from those studies suggested that the successful development of FQ resistance in C. jejuni during antibiotic exposure required an initial cell density of at least 6 log10 CFU/mL and a FQ antibiotic concentration of at least 0.625 µg/mL (or 5X MIC of the strain used). Given that the highest level of C. jejuni detected in pre-treatment rectal feces of this study was around 6–7 log10 CFU/g (likely higher in the intestine) in a few calves prior to the enrofloxacin injection in each of the four treatments groups ( Figure 1 c,e,g,i) and that the concentrations of enrofloxacin (and its metabolite ciprofloxacin) were far above 4 µg/g feces for at least 24 h following the antibiotic injection [ 43 ], it is reasonable to assume that spontaneous FQ-resistant mutants would have been selected if they existed in the calves. Obviously, this was not the case as development of FQ-resistant C. jejuni was not detected in this study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, studies have demonstrated that parenteral delivery of antibiotics also has an impact on the gastrointestinal microbiota [ 55 , 56 ]. In our recent animal study, we observed that the concentrations of subcutaneously administered fluoroquinolones found in feces were several folds higher than that of plasma [ 57 ].…”
Section: Gut Microbiota Immune Development and Fecal Microbiota Trans...mentioning
confidence: 99%